Preliminary design of shrimp pond paddle wheel powered by solar energy - Aljufri Aljufri; Aris Abizar; Revi Syarlian; Adi Setiawan (Jurnal POLIMESIN, 2021)
The level of oxygen solubility in shrimp ponds is crucial for the success of shrimp farming, therefore the farmers need waterwheels to increase levels of dissolved oxygen in the pond. In general, shrimp farmers are still relying on the wheels powered by electricity which is supplied from national grid and diesel engines. To overcome these problems, an alternative solution is needed by utilizing solar energy. This work aims to develop a simple design of paddle-wheel powered by solar energy for shrimp farming waterwheels. The design of this equipment used a 50 Wp photovoltaic panel to turn a 250-Watt electric motor. The electricity generated in the form of DC current, stored in a 50 Ah battery then the DC current is converted into AC current by 1000-Watt inverter. Dissolved oxygen (DO) sensor digital data that is connected to a computer via Arduino Uno was recorded and displayed on the serial monitor and LCD. This equipment has been successfully tested by running directly using solar energy sources for 35 minutes.